Le rôle du passeur ludique et des objets connecteurs dans la participation de l'enfant en situation de handicap à un jeu - Ludovic Blin
This article stemming from an empirical research led in some leisure - centres and during playful meetings wants to highlight the notions of a playful ferryman and border- objects ( Wenger, 2005) .It more exactly deals with the possibility that a third party or objects offer to allow the child in situation of handicap to pass from a community of practice to an other one. Our theoretical frame leans on the concepts of brokers and border- objects developped in Wenger's theory of communities of practice (2005) and theory of fun community of practice (Brougère, 2010).